Occurrence and distribution of tomato seed‐borne mycoflora in Saudi Arabia and its correlation with the climatic variables. Issue 6 (25th June 2014) - Al‐Askar, Abdulaziz A.; Ghoneem, Khalid M.; Rashad, Younes M.; Abdulkhair, Waleed M.; Hafez, Elsayed E.; Shabana, Yasser M.; Baka, Zakaria A.
Summary One hundred samples of tomato seeds were collected in 2011 and 2012 from tomato‐cultivated fields in Saudi Arabia and screened for their seed‐borne mycoflora. A total of 30 genera and 57 species of fungi were recovered from the collected seed samples using agar plate and deep‐freezing blotter methods. The two methods differed as regards the frequency of recovered seed‐borne fungi. Seven fungi among those recovered from tomato seeds, which are known as plant pathogens, were tested for their pathogenicity and transmission on tomato seedlings. The recovery rate of these pathogens gradually decreased from root up to the upper stem, and did not reach to the stem apex. The distribution of tomato seed‐borne fungi was also investigated throughout Saudi Arabia. In this concern, Al‐Madena governorate recorded the highest incidence of fungal flora associated with tomato seeds. The impact of meteorological variables on the distribution of tomato seed‐borne mycoflora was explored using the ordination technique (canonical correspondence analysis). Among all climatic factors, relative humidity was the most influential variable in this regard. Our findings may provide a valuable contribution to our understanding of future global disease change and may be used also to predict disease occurrence and fungal transfer to new uninfected areas.